2013
DOI: 10.1590/s0004-28032013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen Levels in the Peripheral and Mesenteric Venous Blood of Patients With Rectal Carcinoma

Abstract: ContextThe serum carcinoembryonic antigen (CEA) is an important prognostic factor in colorectal cancer, however the rectum presents different routes of venous drainage, stating that the level of CEA in peripheral and mesenteric rectal tumors may be different, depending on the location of the tumor in the rectal segment.ObjectiveThe goal of this study was to evaluate the relationship between the peripheral and mesenteric venous levels of CEA and the association between these levels and the tumour location in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…In fact, previous studies have shown that in patients with CRC, CEA5 levels are higher in the MV than in the PV. 31 , 32 A previous study with a large cohort of patients 20 found a correlation between tumor size and miR-21 expression in PV plasma; our findings are similar, but we observed this correlation only in MV plasma. We also found an association between the anatomic location of the tumor and miR-21 expression levels in both MV and PV plasma, although miR-21 expression was higher in MV than in PV plasma.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, previous studies have shown that in patients with CRC, CEA5 levels are higher in the MV than in the PV. 31 , 32 A previous study with a large cohort of patients 20 found a correlation between tumor size and miR-21 expression in PV plasma; our findings are similar, but we observed this correlation only in MV plasma. We also found an association between the anatomic location of the tumor and miR-21 expression levels in both MV and PV plasma, although miR-21 expression was higher in MV than in PV plasma.…”
Section: Discussionsupporting
confidence: 85%